Designing Welding Workstations to Reduce the Risk of MSDS (Musculoskeletal Disorders) - Machdian Muharam; Maya Arlini puspasari (Publikasi Indonesia, 2024)
This study aims to design an ergonomic welding workstation to reduce the risk of Musculoskeletal Disorders (MSDs) in welding workers at PT. Sinar Bharata Perkasa. The background of this study is the high preval_ence of MSDs in welding workers due to unergonomic work posture. The methods used include posture analysis using Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA), as well as anthropometric calculations to design workstations that suit the physical condition of workers. Data collection was carried out through the Nordic Body Map (NBM) questionnaire and posture measurements before and after the design improvement. The results showed that the new workstation design was able to significantly reduce the risk of MSDs, with a decrease in the RULA score from 6 to 3 and the REBA score from 8 to 3. In conclusion, this new workstation design has the potential to improve the health and productivity of welding workers at PT. Sinar Bharata Perkasa.